Adenosine augments IL‐10‐induced STAT3 signaling in M2c macrophages. Issue 6 (6th August 2013) - Koscsó, Balázs; Csóka, Balázs; Kókai, Endre; Németh, Zoltán H.; Pacher, Pál; Virág, László; Leibovich, S. Joseph; Haskó, György
Abstract : Adenosine signaling augments IL‐10‐induced STAT‐3 dependent gene expression in macrophages, suggesting its role in M2c polarization. Abstract : The alternatively activated macrophage phenotype induced by IL‐10 is called M2c. Adenosine is an endogenous purine nucleoside that accumulates in the extracellular space in response to metabolic disturbances, hypoxia, inflammation, physical damage, or apoptosis. As adenosine is known to regulate classically activated M1 and IL4‐ and IL‐13‐activated M2a macrophages, the goal of the present study was to explore its effects on M2c macrophages. We found that adenosine augmented the IL‐10‐induced expression of TIMP‐1 and arginase‐1 by the mouse macrophage cell line RAW 264.7 and by mouse BMDMs. The effects of AR stimulation on IL‐10‐induced TIMP‐1 or arginase‐1 expression were lacking in A2B AR KO macrophages. The role of A2B AR on TIMP‐1 production of RAW 264.7 cells was confirmed with specific agonist BAY606583 and antagonist PSB0788. AR stimulation augmented IL‐10‐induced STAT3 phosphorylation in macrophages, and pharmacological inhibition or silencing of STAT3 using siRNA reduced the stimulatory effect of AR stimulation on TIMP‐1 production. In contrast to its stimulatory effect on IL‐10‐induced STAT3 activation, adenosine inhibited IL‐6‐induced STAT3 phosphorylation and SAA3 expression. In conclusion, adenosine enhances IL‐10‐induced STAT3 signaling and M2c macrophage activation.